Sunflower fertigated with potassium fertilization in two agricultural seasons in the Brazilian semiarid region - Santos, Allysson; Tartaglia, Francilene; Souza, Almir Rogério; Santos, Manoel; Silveira, Lindomar; Barros Júnior, Aurélio (Revista Ciência Agronômica, 2020)
The objective of this study was to evaluate the effect of potassium doses on the production components of sunflower cultivars grown in the semiarid climate region. The experiment was carried out in two agricultural seasons, in 2016 and 2017, at the Rafael Fernandes Experimental Farm, Mossoró, RN, Brazil. The experimental design used was randomized blocks, in split plots, with four replicates. Five potassium doses were evaluated in the plots: 0, 30, 60, 90 and 120 kg ha-1 of K2O, and four sunflower cultivars were evaluated in the subplots: Aguará 6, Altis 99, Multissol and BRS 122. The evaluated characteristics were: K content in the diagnostic leaf (KDL), thousand-achene weight (TAW), achene yield (AY), oil content (OC) and oil yield (OY). Potassium doses directly influenced agronomic variables, promoting better performance. The best K2O doses for sunflower yield were 77.7 and 80.2 kg ha-1 in the first season for the cultivars Altis 99 and Aguará 6, and 65.9 and 69.5 kg ha-1 in the second season for Altis 99 and Aguará 6. In the first season, the production results were higher than in the second, and the cultivars Aguará 6 and Altis 99 obtained the highest achene yield and oil yield in both agricultural seasons.